The Relationship between burnout and coping to employees in Social Care (Child Protection) - Rus, Mihaela; Sandu, Mihaela Luminita; Preda (Georgescu), Cristina Mădălina; Titorencu, Adrian Cristian (Technium Social Sciences Journal, 2022)
This paper addresses general aspects of burn-out and coping mechanisms in the context of the professional activity of workers in Social care (Child Protection). According to the National Authority for the Rights of Persons with Disabilities, Children and Adoptions (ANDPDCA, 2021), the main responsibilities of Child Protection are the evaluation and monitoring of the special protection measure for children and families. The evaluation and monitoring process involves all the workers in the multidisciplinary team, namely: social workers, psychologists, educators, nurses, etc. and also administrative support staff.